2016
DOI: 10.1177/1076029615625825
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thrombin Generation and Sensitivity to Activated Protein C Among Patients With Myeloma and Monoclonal Gammopathy of Undetermined Significance

Abstract: The etiology of the prothrombotic state in myeloma has yet to be definitively characterized. Similarly, while recent evidence suggests that patients with monoclonal gammopathy of undetermined significance (MGUS) may also be at increased risk of thrombosis, the magnitude and the etiology of this risk have also yet to be defined. The present study aims to characterize patterns of plasma thrombin generation and sensitivity to the anticoagulant activity of activated protein C (APC) at the time of initial diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…With 1 PM TF, no significant difference was found between patients with and controls, which was in agreement with Leiba et al study comparing 13 patients to 14 controls . However, Crowley et al demonstrated an increase in TG in patients with MM, attested by a significantly higher peak thrombin in 8 patients compared with 8 controls …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…With 1 PM TF, no significant difference was found between patients with and controls, which was in agreement with Leiba et al study comparing 13 patients to 14 controls . However, Crowley et al demonstrated an increase in TG in patients with MM, attested by a significantly higher peak thrombin in 8 patients compared with 8 controls …”
Section: Discussionsupporting
confidence: 83%
“…In addition, Tiong et al observed a significant acceleration of TG in 15 patients during treatment, attested by a significant increase in velocity index at 2 months of MM therapy compared with baseline . In contrast, in Crowley et al study including 10 patients before and during myeloma treatment (at 1, 2, and 3 months), thrombin generation was significantly decreased during treatment, as evidenced by a significant decrease in peak thrombin at 3 months of treatment compared with baseline . Similarly, Undas et al also demonstrated a significant decrease in peak thrombin at 3 months of treatment in 48 patients …”
Section: Discussionmentioning
confidence: 96%
“…16 In addition, we did not consistently find higher baseline values of either ETP or peak thrombin in patients with nMM compared to those reported in patients with monoclonal gammopathy of undetermined significance and healthy controls. 15,[17][18][19] The coagulability associated with nMM therefore remains an enigma.…”
Section: Resultsmentioning
confidence: 99%
“…The third limitation concerns the way in which we evaluated TG. In particular, TG assessment under conditions sensitive to the protein C inhibitor system (with addition of exogenously activated protein or thrombomodulin) and/or with the use of different concentrations of TF, might have given different results. Notably, we did not find any differences in TG determined in the presence of platelets (PRP) as opposed to their absence (PPP).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin generation (TG) is being increasingly studied by many groups who perform measurements at baseline and during treatment as well as explore the association with VTE occurrence. Most groups have reported abnormal TG in multiple parameters of the assay compared to healthy controls [56,57]. Data is variable and difficult to compare across studies as different TG assays have been used as well as different TG trigger concentrations and phospholipid reagents.…”
Section: Disease-specific Risk Factors and The Search For A Biomarkermentioning
confidence: 99%